Human resources management in the pandemic age: HR practices and the impact on employee motivation - Abdul Munir, Zarina; Mohd, Hisham; Adha Hafit, Nor Intan; Noranee, Shereen; Omar, Norhayati (UiTM Cawangan Johor, 2021)
Human resources management is vital to the development of human capital and ensuring the increased productivity from employees. The sustainability of employees ' productivity has presented huge challenges to HR departments in establishing morale and motivation among staff, who are dealing with pressures of working from home and parenting. Hence, this study investigates on the influence of training and development, career development and working environment on employee motivation. A total of 136 employees from private organizations were selected to fill out a survey. This data was gathered and analysed through the Partial Least Square (PLS) method. The findings indicate that training and development and career development have no significant impact on employees ' motivation whereas working environment significantly influences the motivation of staff These results show that employers should prioritize ways to improve and address working environment concerns in order to evolve with the present shift in working norms.